Tuberous Sclerosis Presenting With Acute Kidney Failure, Pyelonephritis, and Polycystic Kidney Disease (Iranian Journal of Kidney Diseases, 2014)
Tuberous sclerosis complex (TSC) is a multisystemic inherited autosomal dominant disease characterized by the development of hamartomas in the brain and kidneys. In about 2% of patients, polycystic kidney disease is present, which may result in different stages of renal insufficiency. Acute kidney failure has not been reported in infants with TSC. We report a female infant with TSC who was admitted to hospital with pyelonephritis, acute kidney injury, and polycystic kidney disease.